2004
DOI: 10.1021/om049379e
|View full text |Cite
|
Sign up to set email alerts
|

Ru(xantsil)(CO)(PCy3):  Facile Generation of a Coordinatively Unsaturated Ruthenium(II) Complex Bearing 14 Valence Electrons [xantsil = (9,9-dimethylxanthene-4,5-diyl)bis(dimethylsilyl)]

Abstract: Treatment of Ru(xantsil)(CO)(η6-toluene) (1) [xantsil = (9,9-dimethylxanthene-4,5-diyl)bis(dimethylsilyl)] with PCy3 led to the formation of Ru(xantsil)(CO)(PCy3) (3), in which the xantsil ligand is bound to the ruthenium center in κ3(Si,Si,O) fashion. The highly coordinatively unsaturated nature of 3 is indicated by the reaction with CO to give Ru(xantsil)(CO)3(PCy3) (5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…Cation 1 is obtained in 28 % yield and it can be isolated as the tetrafluoroborate salt (Scheme 1). The substitution of an η 6 -arene ligand at a ruthenium atom by three phosphane ligands has been observed so far for benzene, [4] toluene [5] and pcymene [6] ligands, but never for the strongly bound η 6 -C 6 Me 6 ligand. The single-crystal X-ray structure analysis of [1][BF 4 ], crystallised by slow diffusion of diethyl ether in a concentrated acetone solution of [1][BF 4 ], reveals for cation 1 the presence of three bridging hydrido ligands coordinated to the two ruthenium atoms, one ruthenium atom being coordinated to an η 6 -C 6 Me 6 ligand and the other one to three PMe 3 ligands.…”
Section: Resultsmentioning
confidence: 97%
“…Cation 1 is obtained in 28 % yield and it can be isolated as the tetrafluoroborate salt (Scheme 1). The substitution of an η 6 -arene ligand at a ruthenium atom by three phosphane ligands has been observed so far for benzene, [4] toluene [5] and pcymene [6] ligands, but never for the strongly bound η 6 -C 6 Me 6 ligand. The single-crystal X-ray structure analysis of [1][BF 4 ], crystallised by slow diffusion of diethyl ether in a concentrated acetone solution of [1][BF 4 ], reveals for cation 1 the presence of three bridging hydrido ligands coordinated to the two ruthenium atoms, one ruthenium atom being coordinated to an η 6 -C 6 Me 6 ligand and the other one to three PMe 3 ligands.…”
Section: Resultsmentioning
confidence: 97%
“…As an attempt to provide a higher stability to the catalytic intermediates, the complex [(p-cymene)Ru- [22] considered as a 14-electron synthetic equivalent. The release of the arene ligand is also described in analogous ruthenium complexes of type [(h [23] and it is proposed as the initial step towards the generation of the olefin metathesis catalytically active species from [(h…”
Section: Resultsmentioning
confidence: 99%
“…The coordinatively unsaturated ruthenium xantsil phosphine complex 1 was synthesized via three reaction steps illustrated in Scheme 1 from Ru 3 (CO) 12 and the ligand precursor xantsilH 2 (2) [7,8]. The reaction of Ru 3 (CO) 12 and 2 in toluene at 120 °C for 90 min afforded tetracarbonyl xantsil complex cis-Ru{κ 2 (Si,Si)-xantsil}(CO) 4 (3) in 35 % yield.…”
Section: Preparation Of Catalystsmentioning
confidence: 99%
“…Complex 3 was then heated in refluxing toluene for 5 h to give the η 6 -toluene complex Ru{κ 2 (Si,Si)-xantsil}(CO)(η 6 -toluene) (4) in 95 % yield by substitution of three carbonyl ligands with a toluene molecule [7]. The η 6 -toluene ligand in 4 is substitution labile and can be substituted cleanly with various ligands at room temperature [8]. We have found that the reaction of 4 with a bulky tricyclohexylphosphine resulted in substitution of one phosphine molecule (2-electron donor) for a toluene ligand (6-electron donor) to give complex 1 [8].…”
Section: Preparation Of Catalystsmentioning
confidence: 99%
See 1 more Smart Citation